Relationships between broodstock condition, oocyte quality, and 24 h D-larval survival during the spawning season of the pullet carpet shell Venerupis corrugata (Gmelin, 1791). Issue 4 (1st October 2016) - Joaquim, Sandra; Matias, Domitília; Matias, Ana Margarete; Gonçalves, Rui; Vera, Cátia; Chícharo, Luís; Gaspar, Miguel B.
Abstract: Venerupis corrugata is commercially exploited in Europe. Over-fishing and recruitment failure is causing the decline of its populations and stock sustainability. Knowledge of this species reproduction is paramount to establish hatchery production of juveniles for restoring natural beds. This work aimed to find a relationship between broodstock condition, oocyte quality, and viability of 24 h D-larvae. Adult specimens were induced to spawn by thermal stimulation. From each female, oocytes were taken for biochemical analyses (proteins, total lipids, and carbohydrates), and the remaining oocytes were fertilized. The 24 h D-larval yield was calculated after embryo incubation. Spawning in the hatchery with 'wild' broodstock was possible for a long period, however, subsequent larval viability varied according to oocyte quality. Two distinct periods of spawning were recorded: in January/March, with a higher number of oocytes released, and in June/July with a lower response to the spawning stimulation, however with greater success in 24 h D-larval survival. The condition index of broodstock and the total lipids of oocytes released can be used as benchmarks for estimating the success of D veliger larvae.